Fetal cardiomegaly in a preeclamptic pregnancy: A case report - Muhammad Imam Muttaqien; Donel Suhaimi (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Preeclampsia is a pregnancy-specific condition characterized by hypertension and proteinuria after 20 weeks of gestation. This disorder is associated with endothelial dysfunction, abnormal placentation, and reduced uteroplacental perfusion. Preeclampsia increases the risk of complications for both mother and fetus, including intrauterine growth restriction, preterm birth, and perinatal mortality. In the fetus, placental insufficiency caused by preeclampsia may result in hypoxia and increased cardiac workload, which can subsequently lead to cardiomegaly. Early detection and proper management are essential to reduce morbidity and improve pregnancy outcomes. Purpose: To evaluate the association between preeclampsia and the occurrence of fetal cardiomegaly as detected through prenatal ultrasound. Method: This descriptive analytic study applied a case study approach involving a 20-year-old pregnant woman with preeclampsia who delivered preterm at the Obstetrics and Gynecology Department. Data collection included interviews, physical examinations, medical records, and diagnostic imaging, particularly fetal ultrasound. Ethical principles were followed, and informed consent was obtained from the patient. Data analysis was performed descriptively, comparing clinical findings with theoretical evidence to support discussion and management strategies. Results: Ultrasound examination revealed fetal cardiomegaly accompanied by reversed end-diastolic flow in the umbilical artery, indicating severe compromise of fetal well-being. The patient was closely monitored, and timely delivery was performed. The neonate required immediate neonatal intensive care management due to prematurity and cardiovascular complications. Conclusion: This case highlights the relationship between preeclampsia and fetal cardiomegaly, emphasizing the importance of comprehensive monitoring and timely intervention in high-risk pregnancies. Early recognition and appropriate management can improve maternal and neonatal outcomes in cases complicated by preeclampsia.